(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the theoretical foundations of the concept of pedagogical competence, its core components, and the current qualification requirements for foreign language teachers. The study conducts a comparative analysis of national and international perspectives based on the ideas of prominent scholars such as N.V. Kuzmina, A.B. Khalikov, Brown, Rodgers, Piepho, and Hallet. It also evaluates the significance of international frameworks such as EPOSTL, CEFR, and the Cambridge English Teaching Framework, proposing recommendations for their application in the Uzbek educational system.